Non-silicon defoaming agent, synthetic method and application in field of scandium extraction

The synthesis of non-silicon defoaming agents through the reaction of amino acids and fatty alcohols and triazine substitutions has solved the problem of insufficient toxicity and stability of silicon-type defoaming agents in extraction and extraction, and achieved efficient inhibition of third phase generation and improvement Effects of process stability.

CN119303348AActive Publication Date: 2025-01-14WANHUA CHEM GRP CO LTD

Patent Information

Application Number
CN202411710349.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-01-14
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing silicone defoamers have poor toxicity and biodegradability during the extraction and extraction process, which limits their development in environmentally friendly applications, and the existing non-silicon defoamers are in specific extraction processes. Inadequate stability and selectivity.

Method used

The esterification reaction of amino acids and fatty alcohols is carried out, and then replaced with triazine compounds to synthesize a non-silicon type defoaming agent, which is used as an auxiliary agent during the extraction and extraction of scandium, inhibiting the formation of the third phase and improving process stability.

Benefits of technology

The prepared non-silicon type defoaming agent has high nitrogen content and good chemical and thermal stability. It can effectively inhibit the generation of the third phase during the extraction and extraction process, reduce the phenomenon of mixed phase and emulsification, and improve product purity and process stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a synthesis method of a non-silicon defoaming agent and application of the non-silicon defoaming agent in the field of scandium extraction in hydrometallurgy. The defoaming agent is synthesized by a component A, a component B and a component C through a two-step reaction, the synthesis method comprises the following specific synthesis steps: 1) carrying out esterification reaction on an amino acid substance A and a fatty alcohol substance B to generate an amino ester substance D; and 2) carrying out substitution reaction on the amino ester substance D and a triazine compound C to obtain the non-silicon defoaming agent. The defoaming agent disclosed by the invention is wide in application range, can be applied to links such as a laterite-nickel ore hydrometallurgy front-end scandium extraction method and an MHP hydrometallurgy scandium impurity removal process, is added as an auxiliary agent in the extraction process, and is used for reducing the surface tension of liquid, preventing the formation and enrichment of a third-phase substance and reducing the occurrence of an emulsification phenomenon; the process stability and the output quality are improved, and the method has important industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrometallurgy, and in particular relates to a non-silicon defoaming agent, a synthesis method and application in the field of scandium extraction. Background Art

[0002] Defoamers are widely used in chemical and industrial production. Their main function is to inhibit the formation and stabilization of foam in liquids. In the process of extracting scandium, there are often a large number of surfactants or other organic substances in the liquid phase. These substances are easy to form foam, affecting the reaction and the purity of the product. Therefore, effective defoamers are particularly important in these processes. Traditional defoamers are mostly based on silicon compounds, such as silicone oil, silane derivatives, etc. However, silicon defoamers may have problems such as toxicity or poor biodegradability under certain conditions, which limits their development in environmentally friendly applications. Therefore, the development of a non-silicon, environmentally friendly defoamer has important scientific significance and application value.

[0003] Most of the non-silicon defoamers reported so far are based on polymers or small organic molecules, but their application in the extraction of metals such as scandium is still relatively limited. Although existing defoamers have shown good defoaming effects in some areas, they may face certain challenges in terms of stability, selectivity, and compatibility with the reaction system in specific extraction processes of scandium.

[0004] Therefore, there is an urgent need to develop a new type of non-silicon defoaming agent with the following characteristics: (1) high efficiency defoaming performance, which can effectively inhibit the formation and stabilization of foam in liquids; (2) good environmental friendliness and biodegradability, which can reduce the negative impact on the environment.

[0005] The present invention aims to provide a novel synthesis method of a non-silicon defoamer and its application in the field of scandium extraction, so as to solve the limitations of the prior art and meet the urgent demand for efficient and environmentally friendly defoamers in industrial production. Summary of the invention

[0006] In view of the above problems, the present invention discloses a method for synthesizing a non-silicon defoaming agent, which can be used in the field of scandium extraction as an extractant auxiliary to inhibit the formation of a third phase during the extraction process and improve process stability.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for synthesizing a non-silicon defoamer, wherein the defoamer is synthesized from three components, component A, component B, and component C, through a two-step reaction;

[0009] The specific synthesis steps are:

[0010] 1) Amino acid substance A and fatty alcohol substance B undergo esterification reaction to generate amino ester substance D;

[0011] 2) The amino ester substance D and the triazine compound C undergo substitution reaction to obtain a non-silicon type defoaming agent.

[0012] Preferably, the component A is an amino acid substance, such as one or more of 5-aminovaleric acid (CAS: 660-88-8), 4-aminobutyric acid (CAS: 56-12-2), 3-aminopropionic acid (CAS: 107-95-9), and 6-aminocaproic acid (CAS: 60-32-2).

[0013] Preferably, the B component is a fatty alcohol substance, such as one or more of methanol (CAS: 67-56-1), ethanol (CAS: 64-17-5), and propanol (CAS: 71-23-8).

[0014] Preferably, the C component is an organic heterocyclic compound, preferably a triazine compound, such as 2-chloro-4.6-diamino-1.3.5-s-triazine (CAS: 3397-62-4) and 2-hydroxy-4.6-diamino-1.3.5-s-triazine (CAS: 108-78-1).

[0015] As a preferred embodiment of the process of the present invention, the specific process of the esterification reaction in step 1) is:

[0016] 1) adding an amino acid substance A to a suspension containing a fatty alcohol substance B and a catalyst to obtain a mixture for reaction;

[0017] 2) After the reaction is completed, the heating reflux reaction is continued; after the heating reflux reaction is completed, post-treatment is performed to obtain amino ester substance D.

[0018] The post-treatment comprises the steps of cooling, removing the solvent under reduced pressure, filtering and drying.

[0019] Preferably, the mixing temperature in step 1) is 0-5°C, the amount of amino acid substance D is 0.1-1 mol, the amount of fatty alcohol substance B is 0.5-2 mol, the catalyst is selected from one of SOCl2 (CAS: 7791-09-7) and PCl3 (CAS: 7719-12-2), the amount of catalyst is 0.1-2 mol, and the reaction time is 1-5h.

[0020] Preferably, in step 2), the heating reflux temperature is 40-80° C., and the reflux time is 1-3 h.

[0021] Preferably, the cooling temperature is 20-35°C and the pressure is 1-10 kPa.

[0022] Preferably, the filtration is carried out in a non-polar solvent, and the residue is suspended in a non-polar solvent for filtration. The non-polar solvent is one or more of hexane, n-pentane (CAS: 109-66-0), cyclohexane (CAS: 110-82-7), and dichloromethane (CAS: 75-09-2), and the amount of the non-polar solvent is 50-500 ml.

[0023] Preferably, the drying is vacuum drying, with a vacuum degree ranging from 10 to 100 mmHg, a drying temperature of 30 to 50° C., and a drying time of 16 to 28 hours.

[0024] As a preferred embodiment of the process of the present invention, the specific process of the substitution reaction in step 2) is:

[0025] 1) dissolving the triazine compound C in a solvent, and adding the amino ester substance D obtained in step 1);

[0026] 2) heating the obtained mixture to react, and performing post-treatment after the reaction is completed to obtain a non-silicon type defoaming agent.

[0027] In the present invention, the post-treatment comprises the steps of filtering, concentrating, washing and drying.

[0028] Preferably, the amount of the triazine compound C is 0.01-0.2 mol, the amount of water is 50-300 ml, and the amount of the amino ester substance D is 1-1.5 times the amount of the triazine compound C.

[0029] Preferably, the reaction temperature is 80-130° C. and the reaction time is 12-18 h.

[0030] Preferably, after the reaction is completed, a cooling step is further included, wherein the cooling temperature is 0-5° C. and the cooling time is 1-6 h.

[0031] Preferably, the filtered filtrate is subjected to vacuum concentration, and the vacuum concentration conditions are: temperature 30-60°C, vacuum degree range 1-10kPa, and time 3-5h.

[0032] Preferably, the oily mixture obtained after vacuum concentration is washed with ethanol. The number of washings is not limited, and is preferably 1 to 10 times.

[0033] Preferably, the drying is performed in vacuum, the drying temperature is 30-60° C., the vacuum degree is 1-10 kPa, and the drying time is 10-25 h.

[0034] On the other hand, the present invention provides a non-silicon defoaming agent prepared by the above method.

[0035] Finally, the present invention also provides an application of a non-silicon defoamer in the field of scandium extraction. The prepared non-silicon defoamer is mixed with an extractant solution and subjected to multi-stage countercurrent extraction with a scandium sulfate solution.

[0036] Preferably, the total amount of the non-silicon defoamer added is 0.01-0.1 times the volume of the extractant solution by volume ratio;

[0037] The extractant solution is a mixture of an extractant and solvent oil, wherein the volume content of the extractant is 15-25%;

[0038] Preferably, the extractant is one or more of P204 and P507;

[0039] Preferably, the solvent oil is one or more of light white oil and kerosene;

[0040] Preferably, the conditions of the multi-stage countercurrent extraction are: extraction stage 3-5, temperature 35-55° C., extraction phase ratio O:A=(1-4):1;

[0041] As a preferred embodiment of the process of the present invention, the metal components of the scandium sulfate solution, measured in terms of metal ion concentration, are: Ni 75-100 g / L, Co 3-15 g / L, Mn 0.5-10 g / L, Sc 0.5-1.5 g / L, Mg 0.5-5 g / L, Cu 0.3-5 g / L, Zn 0-5 g / L, Fe 0-1 g / L, Cr 0-0.5 g / L.

[0042] The beneficial effects of the present invention are:

[0043] The present invention uses a non-silicon defoamer as an auxiliary agent. The defoamer contains a melamine group. Due to its high nitrogen content, the defoamer has certain chemical stability and thermal stability. Compared with some traditional defoamers, it has better environmental compatibility and good stability. It can effectively inhibit the generation and enrichment of the third phase in the process of extracting scandium, reduce the generation of mixed phases, emulsification and the like, and achieve the effect of maintaining the stability of the process and improving the purity and quality of the product. DETAILED DESCRIPTION

[0044] The present invention is further described in detail below with reference to examples. However, the following examples are merely simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0045] Raw materials and sources:

[0046] The raw materials of the present invention are amino acid substance A, fatty alcohol substance B, and triazine compound C;

[0047] The amino acid substance A is 5-aminovaleric acid (CAS: 660-88-8, purchased from Zhengzhou Huiju Chemical Co., Ltd., purity 97%, specification 500g / bottle) or 3-aminopropionic acid (CAS: 107-95-9, purchased from Inokai, purity 99%, specification 500g / bottle);

[0048] The fatty alcohol substance B is methanol (CAS: 67-56-1, purchased from Beijing Zeping Technology Co., Ltd., purity 99.9%, specification 500 ml / bottle) or ethanol (CAS: 64-17-5, purchased from Aladdin, purity ≥ 99.7%, specification 500 ml / bottle);

[0049] The triazine compound C is 2-hydroxy-4.6-diamino-1.3.5-s-triazine (CAS: 645-92-1, purchased from Alfa Aesar (China) Chemical Co., Ltd., purity 90%, specification 1g / bag) or 2-chloro-4.6-diamino-1.3.5-s-triazine (CAS: 3397-62-4, purchased from Shanghai Yuanye Biotechnology Co., Ltd., purity 95%, specification 100g / bottle).

[0050] Test method:

[0051] The invention uses nuclear magnetic resonance spectroscopy to characterize the structural characteristics of the synthesized defoaming agent, and the instrument model is Bruker Avance III HD 600 MHz nuclear magnetic resonance spectrometer, from Bruker Company.

[0052] [Example 1]

[0053] A method for synthesizing a non-silicon defoamer, comprising synthesizing component A, component B and component C through a two-step reaction:

[0054] 5-Aminovaleric acid (CAS: 660-88-8) was selected as component A, purchased from Zhengzhou Huiju Chemical Co., Ltd., with a purity of 97% and a specification of 500 g / bottle. Methanol (CAS: 67-56-1) was selected as component B, purchased from Beijing Zeping Technology Co., Ltd., with a purity of 99.9% and a specification of 500 ml / bottle. 2-Hydroxy-4.6-diamino-1.3.5-s-triazine (CAS: 645-92-1) was selected as component C, purchased from Alfa Aesar (China) Chemical Co., Ltd., with a purity of 90% and a specification of 1 g / bag.

[0055] Esterification reaction: Add 0.1 mol 5-aminopentanoic acid to a suspension of 0.5 mol methanol and 0.1 mol SOCl2 in a 0°C water bath. After 1 hour of reaction, the mixture becomes a clear solution and is heated to reflux at 40°C for 1 hour. The mixture is cooled to 20°C and decompressed to 1 kPa. The residue is suspended in 50 ml of n-pentane, the vacuum range is 10 mmHg, and vacuum filtered and dried at 30°C for 16 hours to obtain 5-amino-1-pentanoic acid methyl ester.

[0056] Substitution reaction: 0.01 mol of 2-hydroxy-4.6-diamino-1.3.5-s-triazine was dissolved in 50 ml of water, and 0.01 mol of 5-amino-1-pentanoic acid methyl ester was added; the resulting mixture was heated to 80° C. for reflux reaction for 12 h, cooled in a 0° C. water bath for 1 h, and then the mixture was filtered. The filtrate was concentrated at 30° C. and 1 kPa vacuum conditions for 3 h to obtain an oily mixture, which was washed with 300 ml of ethanol, and the residual ethanol was removed at 30° C. and 1 kPa vacuum conditions for 10 h to obtain a non-silicon type defoamer solid, the structural formula of which is shown in Formula 1.

[0057]

[0058] Formula 1 Non-silicon type defoamer structural formula (Example 1)

[0059] The structural characteristics of the synthesized non-silicon defoamer were characterized by nuclear magnetic resonance spectroscopy, and the instrument model was Bruker Avance III HD 600 MHz nuclear magnetic resonance spectrometer, Bruker Company;

[0060] NMR data: 1H NMR (500 MHz, DMSO-d6) δ7.14 (t, J = 3.8 Hz, 1H), 6.35 (d, J = 6.1 Hz, 2H), 6.24 (d, J = 6.1 Hz, 2H), 3.63 (s, 3H), 3.42 (td, J = 6.3, 3.7 Hz, 2H), 2.33 (t, J = 7.1 Hz, 1H), 1.74–1.55 (m, 4H).

[0061] [Example 2]

[0062] A method for synthesizing a non-silicon defoamer is provided, wherein the components A, B and C are synthesized through two-step reactions:

[0063] 3-Aminopropionic acid (CAS: 107-95-9) was selected as component A, purchased from Inokai, with a purity of 99% and a specification of 500 g / bottle. Methanol (CAS: 67-56-1) was selected as component B, purchased from Beijing Zeping Technology Co., Ltd., with a purity of 99.9% and a specification of 500 ml / bottle. 2-Chloro-4.6-diamino-1.3.5-s-triazine (CAS: 3397-62-4) was selected as component C, purchased from Shanghai Yuanye Biotechnology Co., Ltd., with a purity of 95% and a specification of 100 g / bottle.

[0064] Esterification reaction: Add 1 mol of 3-aminopropionic acid to a suspension of 2 mol of methanol and 2 mol of PCl3 in a 5°C water bath. After 5 hours of reaction, the mixture becomes a clear solution and is heated to reflux at 80°C for 3 hours. The mixture is cooled to 35°C and decompressed to 10 kPa. The residue is suspended in 500 ml of dichloromethane, the vacuum range is 100 mmHg, and vacuum filtered and dried at 50°C for 28 hours to obtain 3-amino-1-propionic acid methyl ester.

[0065] Substitution reaction: 0.2 mol of 2-chloro-4.6-diamino-1.3.5-s-triazine was dissolved in 300 ml of water, and 0.3 mol of 5-amino-1-pentanoic acid methyl ester was added; the resulting mixture was heated to 130° C. for reflux reaction for 18 h, cooled in a 5° C. water bath for 6 h, and then the mixture was filtered. The filtrate was concentrated at 60° C. and 10 kPa vacuum conditions for 5 h to obtain an oily mixture, which was washed with 1000 ml of ethanol, and the residual ethanol was removed at 60° C. and 10 kPa vacuum conditions for 25 h to obtain a non-silicon type defoamer solid, the structural formula of which is shown in Formula 2.

[0066]

[0067] Formula 2 Non-silicon type defoamer structural formula (Example 2)

[0068] The structural characteristics of the synthesized non-silicon defoamer were characterized by nuclear magnetic resonance spectroscopy, and the instrument model was Bruker Avance III HD 600 MHz nuclear magnetic resonance spectrometer, Bruker Company;

[0069] NMR data: 1H NMR (500 MHz, DMSO-d6) δ7.19 (t, J = 3.7 Hz, 1H), 6.38 (d, J = 6.1 Hz, 2H), 6.29 (d, J = 6.1 Hz, 2H), 3.86 (td, J = 6.3, 3.7 Hz, 2H), 3.63 (s, 3H), 2.67 (t, J = 6.2 Hz, 2H).

[0070] [Example 3]

[0071] A method for synthesizing a non-silicon defoamer is provided, wherein the components A, B and C are synthesized through two-step reactions:

[0072] 5-Aminovaleric acid (CAS: 660-88-8) was selected as component A, purchased from Zhengzhou Huiju Chemical Co., Ltd., with a purity of 97% and a specification of 500 g / bottle. Ethanol (CAS: 64-17-5) was selected as component B, purchased from Aladdin, with a purity of ≥99.7% and a specification of 500 ml / bottle. 2-Chloro-4.6-diamino-1.3.5-s-triazine (CAS: 3397-62-4) was selected as component C, purchased from Shanghai Yuanye Biotechnology Co., Ltd., with a purity of 95% and a specification of 100 g / bottle.

[0073] Esterification reaction: Add 0.5 mol of 5-amino-1-pentanoic acid to a suspension of 1 mol of ethanol and 50 ml of SOCl2 in a 2°C water bath. After reacting for 3 hours, the mixture becomes a clear solution and is heated to reflux at 70°C for 2 hours. The mixture is cooled to 30°C and decompressed to 2 kPa. The residue is suspended in 100 ml of cyclohexane, the vacuum range is 40 mmHg, and vacuum filtered and dried at 40°C for 26 hours to obtain 5-amino-1-pentanoic acid ethyl ester.

[0074] Substitution reaction: 0.1 mol of 2-chloro-4.6-diamino-1.3.5-s-triazine was dissolved in 100 ml of water, and 0.12 mol of 5-amino-1-pentanoic acid methyl ester was added; the resulting mixture was heated to 95°C for reflux reaction for 15 hours, cooled in a 2°C water bath for 5 hours, and then the mixture was filtered. The filtrate was concentrated at 40°C and 1.5 kPa vacuum conditions for 4 hours to obtain an oily mixture, which was washed with 800 ml of ethanol, and the residual ethanol was removed at 50°C and 1.5 kPa vacuum conditions for 15 hours to obtain a non-silicon type defoamer solid, the structural formula of which is shown in Formula 3.

[0075]

[0076] Formula 3 Non-silicon type defoamer structural formula (Example 3)

[0077] The structural characteristics of the synthesized non-silicon defoamer were characterized by nuclear magnetic resonance spectroscopy, and the instrument model was Bruker Avance III HD 600 MHz nuclear magnetic resonance spectrometer, Bruker Company;

[0078] NMR data: 1H NMR (500MHz, DMSO-d6) δ7.14 (t, J = 3.7Hz, 1H), 6.27 (s, 3H), 4.10 (q, J = 6.9Hz, 2H), 3.46–3.35 (m, 2H), 2.33 (t, J = 7.0Hz, 1H), 1.73–

[0079] 1.60(m,4H),1.19(t,J=7.0Hz,3H).

[0080] [Example 4]

[0081] Application of a non-silicon defoamer in the field of scandium extraction comprises the following steps:

[0082] 1) The extractant P204 and the light white oil are mixed in a volume ratio of 25:75 to obtain an extractant solution, and the extractant solution is divided into 4 groups with equal volumes, numbered a, b, c, and d, wherein group a does not add an auxiliary agent, group b adds the non-silicon defoamer in Example 1, group c adds the non-silicon defoamer in Example 2, and group d adds the non-silicon defoamer in Example 3, and the addition ratio is 0.05 times the volume of the extractant solution to obtain an extracted organic phase;

[0083] 2) Take four portions of scandium sulfate solution of equal volume and carry out a multi-stage countercurrent extraction with the four groups of extracted organic phases in 1) respectively. The conditions of the multi-stage countercurrent extraction are: 3 extraction stages, 40°C temperature, and extraction phase ratio of O:A=1:1 to obtain a residual water phase and an organic phase loaded with scandium and other metals. In the extraction process of group a, a third phase is obviously generated, and phase separation is difficult. The scandium extraction rate is only 80%. In the extraction process of group b, no third phase is generated, and the scandium extraction rate is 99.97%. In the extraction process of group c, no third phase is generated, and the scandium extraction rate is 99.95%. In the extraction process of group d, no third phase is generated, and the scandium extraction rate is 99.98%.

[0084] 3) The organic and aqueous phases at the phase interface during the extraction of groups a, b, c, and d were placed in a separatory funnel, and a shake bottle experiment was performed using an oscillator. The oscillator parameters were: oscillation frequency 300 rpm, oscillation time 5 min, and the phase separation time was recorded with a stopwatch. For details, see Table 1. The phase separation time with the addition of a defoaming agent was significantly shorter than that without the addition of a defoaming agent.

[0085] Table 1 Evaluation of phase separation time of non-silicon defoamer

[0086]

[0087]

[0088] [Example 5]

[0089] Application of a non-silicon defoamer in the field of scandium extraction comprises the following steps:

[0090] 1) The extractant P507 and the light white oil were mixed in a volume ratio of 15:85 to obtain an extractant solution, and the extractant solution was divided into 4 groups with equal volumes, numbered a, b, c, and d, wherein no auxiliary agent was added to group a, the non-silicon defoamer in Example 1 was added to group b, the non-silicon defoamer in Example 2 was added to group c, and the non-silicon defoamer in Example 3 was added to group d, and the addition ratio was 0.01 times the volume of the extractant solution to obtain an extracted organic phase;

[0091] 2) Take four portions of scandium sulfate solution of equal volume and carry out a multi-stage countercurrent extraction with the four groups of extracted organic phases in 1) respectively. The conditions of the multi-stage countercurrent extraction are: 5 extraction stages, 35°C, and an extraction phase ratio of O:A=4:1. A residual water phase and an organic phase loaded with scandium and other metals are obtained. In the extraction process of group a, a third phase is obviously generated, and phase separation is difficult. The scandium extraction rate is only 75%. In the extraction process of group b, no third phase is generated, and the scandium extraction rate is 99.96%. In the extraction process of group c, no third phase is generated, and the scandium extraction rate is 99.92%. In the extraction process of group d, no third phase is generated, and the scandium extraction rate is 99.93%.

[0092] 3) The organic and aqueous phases at the phase interface during the extraction of groups a, b, c, and d were placed in a separatory funnel, and a shake bottle experiment was performed using an oscillator. The oscillator parameters were: oscillation frequency 300 rpm, oscillation time 5 min, and the phase separation time was recorded with a stopwatch. For details, see Table 2. The phase separation time with the addition of a defoaming agent was significantly shorter than that without the addition of a defoaming agent.

[0093] Table 2 Evaluation of phase separation time of non-silicon defoamer

[0094] sample Phase separation time / s No additives added 129 Add the non-silicon defoamer of Example 1 31 Add the non-silicon defoamer of Example 2 33 Add the non-silicon defoamer of Example 3 32

[0095] [Example 6]

[0096] Application of a non-silicon defoamer in the field of scandium extraction comprises the following steps:

[0097] 1) The extractant P204 and the light white oil are mixed in a volume ratio of 25:75 to obtain an extractant solution, and the extractant solution is divided into 4 groups with equal volumes, numbered a, b, c, and d, wherein no auxiliary agent is added to group a, the non-silicon defoamer in Example 1 is added to group b, the non-silicon defoamer in Example 2 is added to group c, and the non-silicon defoamer in Example 3 is added to group d, and the addition ratio is 0.1 times the volume of the extractant solution to obtain an extracted organic phase;

[0098] 2) Take four portions of scandium sulfate solution of equal volume and carry out a multi-stage countercurrent extraction with the four groups of extracted organic phases in 1) respectively. The conditions of the multi-stage countercurrent extraction are: 4 extraction stages, 55°C, and an extraction phase ratio of O:A=2:1. A residual water phase and an organic phase loaded with scandium and other metals are obtained. In the extraction process of group a, a third phase is obviously generated, and phase separation is difficult. The scandium extraction rate is only 78%. In the extraction process of group b, no third phase is generated, and the scandium extraction rate is 99.97%. In the extraction process of group c, no third phase is generated, and the scandium extraction rate is 99.95%. In the extraction process of group d, no third phase is generated, and the scandium extraction rate is 99.94%.

[0099] 3) The organic and aqueous phases at the phase interface during the extraction of groups a, b, c, and d were placed in a separatory funnel, and a shake bottle experiment was performed using an oscillator. The oscillator parameters were: oscillation frequency 300 rpm, oscillation time 5 min, and the phase separation time was recorded with a stopwatch. For details, see Table 3. The phase separation time with the addition of a defoaming agent was significantly shorter than that without the addition of a defoaming agent.

[0100] Table 3 Evaluation of phase separation time of non-silicon defoamer

[0101] sample Phase separation time / s No additives added 133 Add the non-silicon defoamer of Example 1 28 Add the non-silicon defoamer of Example 2 27 Add the non-silicon defoamer of Example 3 31

[0102] [Comparative Example]

[0103] 1) The extractant P204 and kerosene are mixed in a volume ratio of 25:75 to obtain an extractant solution, and the extractant solution is divided into two groups with equal volumes, numbered a and b, wherein the non-silicon defoamer in Example 1 is added to group a, and sodium N-oleoyl sarcosinate (a common non-silicon defoamer) is added to group b, and the addition ratio is 0.05 times the volume of the extractant solution to obtain an extracted organic phase;

[0104] 2) taking two portions of the same volume of the scandium sulfate solution, respectively, and subjecting them to a multi-stage countercurrent extraction with the four groups of extracted organic phases in 1), wherein the conditions of the multi-stage countercurrent extraction are: 3 extraction stages, 45° C., and an extraction phase ratio of O:A=3:1, to obtain a raffinate aqueous phase and an organic phase loaded with scandium and other metals, wherein no third phase is produced during the extraction process of group a, and the scandium extraction rate is 99.91%, and the scandium extraction rate of the weakly mixed phase during the extraction process of group b is 96.95%;

[0105] 3) The organic and aqueous phases at the phase interface during the extraction of groups a and b were placed in a separatory funnel, and a shake bottle experiment was performed using an oscillator. The oscillator parameters were: oscillation frequency 300 rpm, oscillation time 5 min, and the phase separation time was recorded with a stopwatch. See Table 4 for details. The phase separation effect of the non-silicon defoamer in Example 1 was better than that of the common non-silicon defoamer.

[0106] Table 4 Evaluation of phase separation time of different defoamers

[0107] sample Phase separation time / s Add the non-silicon defoamer of Example 1 31 Add sodium N-oleoyl sarcosinate 55

Claims

1. A method for synthesizing a non-silicon defoamer, wherein the defoamer is synthesized from three components, component A, component B, and component C, through a two-step reaction; The specific synthesis steps are: 1) Amino acid substance A and fatty alcohol substance B undergo esterification reaction to generate amino ester substance D; 2) The amino ester substance D and the triazine compound C undergo substitution reaction to obtain a non-silicon type defoaming agent.

2. The synthesis method according to claim 1, characterized in that The component A is an amino acid substance, such as one or more of 5-aminopentanoic acid (CAS: 660-88-8), 4-aminobutyric acid (CAS: 56-12-2), 3-aminopropionic acid (CAS: 107-95-9), and 6-aminocaproic acid (CAS: 60-32-2); and / or the component B is a fatty alcohol substance, such as one or more of methanol (CAS: 67-56-1), ethanol (CAS: 64-17-5), and propanol (CAS: 71-23-8); and / or the component C is an organic heterocyclic compound, preferably a triazine compound, such as one of 2-chloro-4.6-diamino-1.3.5-s-triazine (CAS: 3397-62-4) and 2-hydroxy-4.6-diamino-1.3.5-s-triazine (CAS: 108-78-1).

3. The synthesis method according to claim 1 or 2, characterized in that: The specific process of the esterification reaction in step 1) is: 1) adding an amino acid substance A to a suspension containing a fatty alcohol substance B and a catalyst to obtain a mixture for reaction; 2) After the reaction is completed, the heating reflux reaction is continued; after the heating reflux reaction is completed, post-treatment is performed to obtain amino ester substance D.

4. The synthesis method according to claim 3, characterized in that In step 1), the mixing temperature is 0-5°C, the amount of amino acid substance D is 0.1-1 mol, the amount of fatty alcohol substance B is 0.5-2 mol, the catalyst is selected from one of SOCl2 (CAS: 7791-09-7) and PCl3 (CAS: 7719-12-2), the amount of catalyst is 0.1-2 mol, and the reaction time is 1-5h; and / or, the heating reflux temperature in step 2) is 40-80°C, and the reflux time is 1-3h.

5. The synthesis method according to any one of claims 1 to 4, characterized in that The specific process of the substitution reaction in step 2) is: 1) dissolving the triazine compound C in a solvent, and adding the amino ester substance D obtained in step 1); 2) heating the obtained mixture to react, and performing post-treatment after the reaction is completed to obtain a non-silicon type defoaming agent.

6. The synthesis method according to any one of claims 1 to 5, characterized in that The amount of triazine compound C is 0.01-0.2 mol, the amount of water is 50-300 ml, the amount of amino ester substance D is 1-1.5 times the amount of triazine compound C; and / or, the reaction temperature is 80-130° C., and the reaction time is 12-18 h.

7. The non-silicon defoamer obtained by the synthesis method according to any one of claims 1 to 6.

8. Use of the non-silicon defoamer obtained by the synthesis method according to any one of claims 1 to 6 or the non-silicon defoamer according to claim 7 in the field of scandium extraction, mixing the prepared non-silicon defoamer with an extractant solution and performing multi-stage countercurrent extraction with a scandium sulfate solution.

9. The use according to claim 8, characterized in that The total amount of non-silicon defoamer added is 0.01-0.1 times the volume of the extractant solution according to the volume ratio; and / or, the extractant solution is a mixture of extractant and solvent oil, wherein the volume content of the extractant is 15-25%; and / or, the extractant is one or more of P204 and P507; and / or, the solvent oil is one or more of light white oil and kerosene.

10. The use according to claim 8 or 9, characterized in that: The conditions of the multi-stage countercurrent extraction are: 3-5 extraction stages, 35-55°C temperature, and an extraction phase ratio of O:A=(1-4):1; and / or, the metal components of the scandium sulfate solution, in terms of metal ion concentration, are: Ni 75-100g / L, Co 3-15g / L, Mn 0.5-10g / L, Sc 0.5-1.5g / L, Mg0.5-5g / L, Cu 0.3-5g / L, Zn 0-5g / L, Fe0-1g / L, Cr 0-0.5g / L.

Citation Information

Patent Citations

  • Method for synthesizing citric acid ester type compound

    CN101830803A

  • Aminotriazine condensation product, use of an aminotriazine condensation product and method for the production of an aminotriazine condensation product

    CN1764680A

  • Method for reducing foam in a blood substance and antifoaming agents

    US5897548A

Cited By

  • Method for extracting scandium impurity in MHP wet process and producing scandium oxide

    CN120698492A

  • High-stability non-silicon defoaming agent and preparation method thereof

    CN120754574A

  • High-stability non-silicon defoamer and preparation method thereof

    CN120754574B